RIAU MALAY ETHNOPARENTING ON CHILDREN AGED 4-6 YEARS IN THE BUKIT PAYUNG TRANSMIGRATION AREA IN KAMPAR - Farah Nurhaliza; Ria Novianti; Defni Satria (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the activities that are related to parenting, which is interrelated with a culture in order to be described through the point of view based on the indigenous people. The research uses a qualitative approach with ethnographic methods. Data were collected through an interview process and subsequently were analyzed by using the Nvivo 12.2 Software coding technique. The Malay ethnoparenting based on Tunjuk Ajar Melayu through the "Twenty-Five Principles" of parents in Bukit Payung village indicates a significant influence on children in socializing with people around them and the environment where they live. Parenting that was applied by people of different ethnicities has differences between families. Nevertheless, similarities that were found in the research were the values contained within and became the main values in the parenting process. The research result reveals that Riau Malay ethnoparenting, which was applied in the transmigration area of Bukit Payung village, specifically prioritized religious values as one of the main foundations, tolerance for differences, humility towards others, integrity and courage, and providing space for the social environment in forming a cultural identity for children.